DOI: 10.33540/249
|View full text |Cite
|
Sign up to set email alerts
|

Singing as a figure of speech, music as punctuation

Abstract: Table of contents Acknowledgments General introductionThe Musical Foregrounding Hypothesis (MFH) Sub-hypotheses to be tested Song, singing, performance and other definitions A multi-disciplinary approach Preference rules and processing fluency Participants and stimuli Gold MSI and other subject factors Overview 1. The MFH checked against existing research 1.1 The MFH in musicology and literary research 1.1.1 The relationship between words and music in a song 1.1.2 Musical meaning 1.1.3 Song and literariness 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 301 publications
(571 reference statements)
1
9
0
Order By: Relevance
“…Other limitations are that some (but not all) of the benefits are only perceived benefits (see also the recall scores in Schotanus, Eekhof and Willems, 2018), and that the lack of stimulus variation hampers generalization. Schotanus (2020b) provides additional research addressing some of these issues, for example, an analysis of the EEG measures taken within the laboratory study, showing the effect of out-ofkey notes and voiceless intervals (see also Schotanus, Eekhof, and Willems, 2018). Furthermore, a second classroom experiment was conducted, in which accompanied songs performed by various artists turned out to support recall for the content of the songs (Schotanus, 2020b, p. 305-324).…”
Section: Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Other limitations are that some (but not all) of the benefits are only perceived benefits (see also the recall scores in Schotanus, Eekhof and Willems, 2018), and that the lack of stimulus variation hampers generalization. Schotanus (2020b) provides additional research addressing some of these issues, for example, an analysis of the EEG measures taken within the laboratory study, showing the effect of out-ofkey notes and voiceless intervals (see also Schotanus, Eekhof, and Willems, 2018). Furthermore, a second classroom experiment was conducted, in which accompanied songs performed by various artists turned out to support recall for the content of the songs (Schotanus, 2020b, p. 305-324).…”
Section: Further Researchmentioning
confidence: 99%
“…IN Schotanus (2020a), I reported on two studies, a classroom study and a laboratory experiment involving EEG measures, in which participants listened to different song versions of the same four songs and answered some questions about them (see also Schotanus, Eekhof and Willems, 2018). The studies were created in order to test several aspects of the Musical Foregrounding Hypothesis (Schotanus 2015(Schotanus , 2020b, including the assumption that presenting a text sung instead of spoken would support text processing, even after just one exposure, in particular in a classroom setting. In his commentary, Lee focuses on the latter hypothesis as if it were the main one, which may have coloured his interpretation of the study.…”
mentioning
confidence: 99%
“…It is not sure, however, whether on-beat silences in the voice part are indeed perceived as loud rests if the accompaniment continues. Schotanus (2020b, Chapter 3.2) did not even find on-beat silences in a cappella songs to be perceived as loud rest. However, Temperley (2009) has found that in polyphonic music an onset in a metrically weak position is more likely to be succeeded by an onset in a metrically strong position in the same stream than in a different stream or by a rest, and Witek, Clarke, Kringelbach, & Vuust, et al (2014) have shown that syncopations of one stream within a polyphonic stimulus destabilize a rhythmic pattern even if events in other sound streams occur on-beat.…”
mentioning
confidence: 96%
“…One example of these “affects” is sincerity (which has been mentioned by Pattison [2015]). Other interactive emotional communication through music may involve a nagging or a calming quality, which is defined by the effect on the listener (Schotanus, 2020a, 2020b, Part 3), and social or psychological constructions (Warrenburg, 2020) such as the impression of authenticity, which is very important in the music industry (Auslander, 1999; Frith, 1981/2007). Authenticity and sincerity may not seem to be directly related to emotion, yet, if a singer is interpreted to be inauthentic or insincere, this will affect both the listener’s interpretation of the emotional state of the singer and the listener’s own emotional state, and consequently it will also affect the listener’s ability to connect with the music.…”
mentioning
confidence: 99%
See 1 more Smart Citation